Glass slipper, gold sandal : a worldwide Cinderella - Fleischman, Paul (H. Holt, 2007)
The author draws from a variety of folk traditions to put together this version of Cinderella, including elements from Mexico, Iran, Korea, Russia, Appalachia, and more.